Online-Based Simple Cooperative Learning Design (SCL-D) for Accounting - Mentari, Sriyani; Andayani, Endang Sri; Sulikah, Sulikah; Nagari, Primasa Minerva (Fakultas Ekonomi, Universitas Negeri Semarang, 2021)
This paper aims to provide an alternative design for Simple Cooperative Learning on online learning by accommodating a variety constraints and difficulties faced by teachers and students and answer weaknesses of existing methods. This study used research and development method using ADDIE (Analysis, Design, Development, Implementation, and Evaluation) design to produce an online-based cooperative learning model, namely SCL-D (Simple Cooperative Learning Design). The survey was conducted on a sample of 153 students at state and private vocational schools in Malang city. The results of this research are a learning model. Therefore, this method is suitable for completing research objectives, namely producing an SCL-D learning model that is suitable for learning accounting for vocational high schools with 3M requirements ‘easy, cheap, and attractive’. Online-based learning has many advantages as well as weaknesses. Various e-learning platforms make it easy for teachers and students to interact in online learning. The teacher's ability to design attractive distant learning is a determining factor for the success of the learning process. The test results of the SCL-D model show that through this simple cooperative learning design improves student learning achievement.